TECHNOLOGY OF COMBINED IRRIGATION OF VEGETABLE CROPS - E. V. Melikhova (Овощи России, 2019)
There are no doubts about the advantages of using drip irrigation, however, it does not solve the problem of regulating plant phytoclimate in open ground during periods of high temperatures in the Lower Volga region when the biological development of vegetable crops is inhibited, which leads to a decrease in yield. The use of combined irrigation in the combination of drip and fine solves the problem of reducing thermal stress and increases moisture on the soil surface. Based on the research and publications of Russian scientists, the main requirements for the functioning of combined irrigation systems have been identified. These include the provision of drip and fine (aerosol) irrigation, the system should work both jointly and separately, the regulation of plant phytoclimate, the possibility of using foliar feeding and chemical protection, etc. To solve this problem, a number of technical solutions have been considered, which will allow to partially or fully satisfy all the requirements for the stability of the technological process of growing crops under combined irrigation and eliminate the above-mentioned negative environmental conditions of the Lower Volga region. The FGBNU VNII “Raduga” developed the KAU-1M aerosol humidification kit, and the scientists of the Volgograd State Agrarian University developed technical solutions Spray Nozzle of the Combined Irrigation System for Cultivation of Vegetable Crops). The proposed technical solutions for the combined irrigation system will improve operational reliability, provide the plants with soil moisture, control the temperature, nutritional regime of the plants, which will make it possible to obtain stable yields of agricultural crops and environmental safety of the environment.